PATTERN OF COMPUTED TOMOGRAPHY FINDINGS IN ADULT PATIENTS PRESENTING WITH STROKE IN NNEWI, SOUTHEAST NIGERIA - Nnamdi, Oluchukwu Faith; Ugwuanyi, Daniel C.; Eze, Joseph C; Ukibe, Nkiru R.; Elugwu, Chukwuemeka Henry; Obinna, Obiedo Kingsley (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2023)
The incidence of stroke in developing countries like Nigeria is expected to rise in the future as the population undergoes a “health transition”, from less of infectious diseases, and diseases related to poverty and malnutrition to more of non-communicable diseases. This study sort to evaluate the pattern of computed tomography findings in adult patients presenting with stroke in Nnewi, Southeast Nigeria in order to provide the baseline data that will enable accurate diagnosis in patients affected by stroke. This was a retrospective cross-sectional review. A convenient sampling technique was used to recruit patients’ data with clinical suspected CVA and retrieve records/cases of CT examination findings from this population at Waves diagnostics Nnewi, Anambra state. Statistical package for social science (SPSS) V.20.0 was used to analyse the data include descriptive statistics such as mean, frequency and percentage was used to summarize the data. Data was categorized according to age group and gender. Majority of the participant where in the age range of 51-60years (25%) followed closely by 61-70years (22%) and then 71-80years (19.0%) making age range 51-80years the most stroke affected population (66%). Majority of the participants where males (51%). Result also showed that majority of the participants were diagnosed with right ischaemic CVA (72%) whereas the least was bilateral haemorrhagic CVA (1.0%). In general, ischaemic CVA had the highest prevalence (74.7%). Ischaemic stroke was prevalent in this population, more men had stroke than women especial bilateral CVA (multiple affectation). CVA was more prevalent in the older age group than in the younger population. While basal ganglia lacunar was common feature in ischaemic CVA, intracerebral/subdural haemorrhage and subarachnoid haemorrhage were common features in haemorrhage CVA.